HistoScanningTM vs. standard multifocal biopsy for prostate cancer diagnosis: a comparison of diagnostic methods - S. V. Kotov; R. I. Guspanov; S. A. Pulbere; A. G. Yusufov; A. L. Khachatryan; I. S. Badretdinov; M. S. Zhilov; E. M. Alekberov; S. L. Logvinova (Вестник урологии)
Introduction. Prostate cancer (PCa) is one of the most common malignant diseases. The prostate biopsy is the verification standard of PCa. The multifocal biopsy under ultrasound (US) guidance shows high rate of false negative results. As a result, the new diagnostic methods have been discovered. HistoscanningTM is the new method of visualization. HistoscanningTM is a new prostate tissue differentiation technology based on US backscatter analysis. The software analyses tissue density builds a 3D model of the prostate and indicates the localisation of PCa-suspect foci that are targeted for biopsy.Objective. To rate the diagnostic accuracy of HistoscanningTM and identify the benefits of targeted prostate biopsy compared to the multifocal biopsy.Matherials & methods. A prospective study conducted between Jan 2017 and May 2021 is presented. Ninety-hundred nine patients who underwent transrectal prostate biopsy in Pirogov City Clinical Hospital No. 1 were included. Control group A — 443 men after standard multifocal biopsy, comparison group B — 506 men after combined standard multifocal biopsy together with targeted biopsy using HistoscanningTM.Results. In the control group, prostate cancer was detected in 33.4% of patients, while in the group using the HistoscanningTM device it was found in 39.7%. ISUP 1 high-grade PCa were more frequent in group В — 71.1%, in group А— 52.7%. Isolated lesion of targeted biopsy specimens was found only in 9 patients (4.5%) of the group В. Combined lesion of standard and targeted biopsy specimens was more frequent and was detected in 121 patients. However, in 72 patients no atypical cells were detected in targeted biopsy specimens when prostate cancer was verified in standard biopsy specimens. The efficacy of HistoscanningTM was comparable to standard biopsy for prostate volumes > 60 cс.Conclusion. The use of HistoscanningTM improves the diagnosis of PCa, mainly due to the ISUP 1. Performing only targeted cores is impractical due to the high percentage of false negative results. Combined prostate biopsy with mandatory sampling of targeted biopsy cores along with standard biopsy specimens is indicated. The diagnostic accuracy of HistoscanningTM showed the best results with a prostate volume <60 cc.